Analisis Kasus Pembiayaan Murabahah dan Dampaknya terhadap Kinerja UMKM: Studi Kasus pada UMKM Dilola Snack Medan - Bebyola Fransisca Sibarani; Abi Waqqosh; Darmaida Sari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research was conducted to evaluate the impact of Murabahah financing on the performance of MSMEs, with a case study of Dilola Snack in Medan. Murabahah financing has become one of the main choices for MSMEs in meeting their working capital needs because of its transparent nature and in accordance with sharia principles. In an economic context that continues to develop, MSMEs often face challenges in accessing financing that is in accordance with Islamic values. Therefore, it is important to understand the extent to which this financing can support the growth and sustainability of small businesses. The method used in this research is observation and in-depth interviews with the owner of Dilola Snack to obtain relevant and comprehensive data. The research results show that Murabahah financing has a significant positive impact on increasing production capacity, operational efficiency and new product development. However, margin payment obligations require careful cash flow management to maintain business sustainability. Overall, Murabahah financing has been proven to support the growth of MSMEs while still complying with sharia principles.